2021
DOI: 10.1210/endocr/bqab095
|View full text |Cite
|
Sign up to set email alerts
|

The Cholesterol Metabolite 27HC Increases Secretion of Extracellular Vesicles Which Promote Breast Cancer Progression

Abstract: Cholesterol has been implicated in the clinical progression of breast cancer, a disease that continues to be the most commonly diagnosed cancer in women. Previous work has identified the cholesterol metabolite, 27-hydroxycholesterol (27HC), as a major mediator of the effects of cholesterol on breast tumor growth and progression. 27HC can act as an estrogen receptor (ER) modulator to promote the growth of ERα+ tumors, and a liver x receptor (LXR) ligand in myeloid immune cells to establish an immune-suppressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 74 publications
3
22
0
Order By: Relevance
“…In cancer, both genetic- and diet-induced obesity models have elevated peripheral and pulmonary neutrophils that promote breast cancer metastasis to the lung in a GM-CSF–dependent manner ( McDowell et al, 2021 ; Quail et al, 2017 ). Similar findings have been reported in murine models of high fat diet–induced hypercholesterolemia, where the cholesterol metabolite 27-hydroxycholesterol supports neutrophil recruitment to distal sites to promote metastasis ( Baek et al, 2021 ; Baek et al, 2017 ; Ma et al, 2020 ). Consistently, it has been shown that a high-fat diet promotes the accumulation of Gr1 + myeloid cells within multiple tissues concomitant with suppressed CD8 + T cells and enhanced cancer progression ( Clements et al, 2018 ; Ringel et al, 2020 ; Xia et al, 2011 ).…”
Section: The Unheeded Complexity Of Neutrophil Heterogeneity In Cancersupporting
confidence: 84%
“…In cancer, both genetic- and diet-induced obesity models have elevated peripheral and pulmonary neutrophils that promote breast cancer metastasis to the lung in a GM-CSF–dependent manner ( McDowell et al, 2021 ; Quail et al, 2017 ). Similar findings have been reported in murine models of high fat diet–induced hypercholesterolemia, where the cholesterol metabolite 27-hydroxycholesterol supports neutrophil recruitment to distal sites to promote metastasis ( Baek et al, 2021 ; Baek et al, 2017 ; Ma et al, 2020 ). Consistently, it has been shown that a high-fat diet promotes the accumulation of Gr1 + myeloid cells within multiple tissues concomitant with suppressed CD8 + T cells and enhanced cancer progression ( Clements et al, 2018 ; Ringel et al, 2020 ; Xia et al, 2011 ).…”
Section: The Unheeded Complexity Of Neutrophil Heterogeneity In Cancersupporting
confidence: 84%
“…It seems that the conclusion contradicts with most of the results from animal or in-vitro experiments and the reason is far from clear. Similarly, many reports show that cholesterol promoted carcinogenesis, progression, proliferation and chemo/ radioresistance of breast cancer (Brindisi et al, 2020;Baek et al, 2021;González-Ortiz et al, 2021) while data of these studies showed that ezetimibe has a trend of increasing risk of breast cancer (Fig. 2b).…”
Section: Discussionmentioning
confidence: 62%
“…27‐HC is an abundant cholesterol metabolite in human circulation. Studies have demonstrated that 27‐HC functions as an endogenous oestrogen receptor agonist and its increased expression is associated with a poor prognosis of breast cancer [173,174]. A large‐scale clinical study by Borgquis et al.…”
Section: Discussionmentioning
confidence: 99%
“…27-HC is an abundant cholesterol metabolite in human circulation. Studies have demonstrated that 27-HC functions as an endogenous oestrogen receptor agonist and its increased expression is associated with a poor prognosis of breast cancer [173,174]. A large-scale clinical study by Borgquis et al demonstrated that patients treated with cholesterol-lowering drugs such as statins and non-statins showed a better response to Tamoxifen; the drug effect may be owing to the attenuated oestrogen receptor signalling by the reduction in 27-HC level.…”
Section: Discussionmentioning
confidence: 99%